QUANTITATION OF INTERCELLULAR CONNECTIONS BETWEEN SPERMATOGONIA IN THE MOUSE - Cook, Kenneth (East Carolina University, 2017)
Spermatogonial stem cells (SSCs) are critical in the male reproductive process, as they can either self-renew or proliferate into progenitor cells that differentiate to enter meiosis and eventually form functional sperm. All male germ cells after the stem cell stage are connected through intercellular bridges that result from incomplete cytokinesis. The Geyer laboratory recently discovered the presence of numerous thin cytoplasmic extensions protruding from mouse spermatogonia. We hypothesize that these structures are not the classically described bridges, are unique to spermatogonia, and connect adjacent spermatogonia with a shared cytoplasm. In order to measure the structure of these extensions, we have performed a variety of experiments. We employed a variety of antibodies against protein markers that are characteristic of the fate of spermatogonia, and quantified the numbers of connections between them. CDH1, ID4, and GFRA1 are proteins expressed in undifferentiated spermatogonia, while KIT is expressed in differentiating spermatogonia, and DDX4 is expressed in all germ cells. SEM microscopy confirmed that these extensions are cytoplasm-filled, and that they connect spermatogonia. The dimensions of intercellular bridges in mouse spermatogonia are approximately 1 μm in length x 1 μm in width; therefore, these extensions are clearly unique, since they are much thinner and range in length from about 5 μm to 30 μm in length. Quantification of extensions revealed that they generally connect spermatogonia of the same cellular fate (e.g. undifferentiated or differentiating). Now that we have described these cytoplasmic extensions as patent connections between adjacent spermatogonia, there are a number of potential roles that must be explored in future studies.
Keywords: Differentiating spermatogonia; cytoplasmic connections; spermatogonia; differentiated; self-renewal.